Family Empowerment in Handling Limited Range of Motion of Extremities in Stroke Patients in Gheo Ghoma Village, Ende Regency - Maria Salestina Sekunda; Rifatunnisa; Yustina Pacifica Maria Paschalia (Pascasarjana Universitas Mataram, 2025)
Post-stroke care is the most difficult and longest type of care, requiring patience and calmness from both the patient and the patient's family. The goal of ROM (Range of Motion) exercises is to help clients build strength and maintain joint mobility. The methods used include providing information and simulating a range of motion exercises, which are then demonstrated again by family members. The community service activities were carried out over 2 days, on August 8-9, 2025, in Gheo Ghoma village. The results of the community service showed that most members were not aware of the range of motion and had never conducted ROM exercises for stroke patients. 85% of respondents had limited knowledge, and after receiving material on stroke management, knowledge increased to 92%. As for skills, in the pre-test stage, data showed that all respondents did not know how to manage stroke through a range of motion exercises, which was 92%, and in the post-test stage, results showed an improvement. Therefore, cooperation between families, healthcare workers, and village officials needs to be strengthened to help care for stroke patients.